(untitled) (Journal of Rashid Latif Medical College, 2025)
Objective: A serious public health issue is the general population's lack of understanding, ignorance, and ubiquity of myths and misconceptions about breast and cervical cancers (CCs). The purpose of this study was to assess people's knowledge and attitudes on cancer, specifically with regard to breast and cervical malignancies. Methodology In Lahore, Pakistan, a cross-sectional survey with a descriptive focus was administered to 345 individuals. Data on demographics, exposure to chemical and biological carcinogens, lifestyle choices, and individual behaviors were gathered using a pretested, standardized questionnaire. The study population was examined in relation to important factors using frequency distribution and proportions. Results: Cancer awareness and early detection play crucial roles in reducing morbidity and mortality. This descriptive cross-sectional study assessed public awareness and perceptions regarding cancer, particularly breast and cervical cancers, in Lahore. A total of 298 participants were surveyed, with an average age of 25.19 years. Males comprised 52.0% and females 48.0% of the respondents. Mass media (34.6%), schools (28.5%), and health professionals (6.7%) were the primary sources of cancer-related information. While 72.8% of participants reported fear upon first hearing about cancer, 66.7% believed it is preventable. Only 4.7% had undergone cervical cancer screening, indicating low participation in preventive measures. Additionally, 98.1% of respondents had never smoked, though awareness of smoking-related cancer risks was limited to 66.7%. These findings highlight the need for increased public education, awareness campaigns, and access to screening programs to improve early detection and treatment outcomes in Lahore. Conclusion: In Lahore, Pakistan, there is still a lack of awareness and education regarding cancer, especially breast and cervical cancers. The following prioritized risk factors must be addressed in the public health education campaigns’ sexual and reproductive health component: early onset of sexual intercourse, low level of disease knowledge, and unhealthy lifestyles.